(untitled) (Romanian Journal of Analytic Philosophy, 2025)
K. Stanford (2006, 2009) has offered an antirealist argument (the “problem of unconceived alternatives”, PUA) based on the argument that scientists are not able to grasp alternatives to a current scientific theory T. According to PUA, the mere existence of some epistemically inaccessible alternatives (T’, T”, …) weakens our trust in T and shakes the foundations of mainstream scientific realism. The realist may entertain the inkling that inter-theoretical relations (both existing and expected or ‘hoped-for’) play a role in accepting or rejecting PUA. The most celebrated intertheoretical relations, such as consilience, reduction, realization, emergence, equivalence, or approximation—whether prospective, expected, or realized—bear relevance to the conceivability of their alternatives. This paper presents an ‘eliminative inference’ based on an ‘unification posit’ that weakens the PUA. We employ first a minimal model of inter-theoretical unification couched in terms of the ‘term identification’ of the theoretical terms of two initially different theories, T1 and T2. Then we rethink unification as an ‘ideological identification’ where predicates in different theories are identified. Finally, we can envision a more sophisticated unification as entailment relations among T1 and T2 and their empirical grounds. In all these cases, we propose scenarios of inconceivability based on a minimal consistency requirement run against the “syntactic view” of scientific theories. The upshot of this mechanism is that some alternatives to T1, which remain unconceived within the conceptual and ideological space of T1, can be eliminated because they are inconsistent with empirical constraints on T2. The overall space of ‘serious’ alternatives to both theories is ‘thinned.’ Consistency is a requirement that conditions inter-theoretical relations, mainly when the overlapping evidence supports theories. This argument illustrates in what sense PUA is lessened when scientists or scientific communities operate based on theoretical posits.